Causes of International Migration of Educated Youths from Peri-Urban City of Kathmandu - Shrestha, Mahesh; Rana, Anil (Baneshwor Campus Journal of Academia, 2023)
This research was conducted in Chandragiri Municipality-13 to explore the following objectives; to describe the factors and forces that lead educated youths from developing countries to leave their countries and go abroad, to examine the consequences of such migrations in the study area of Chandragiri particularly. In-depth interviews was used to collect primary information from migrant students and their family members in the study area. It was Purposive sampling methods to select my participants for the study. Fourteen respondents were selected for an interview by using saturation method. There was seven migrants and seven migrant’s parents among the respondents. This paper includes the findings that lack of better opportunity, social structure, and networking with peer’s migrants are major forces that influence the educated youths to go abroad for study. The study area has more negative consequences than positive from youth’s migration to developed countries like low chances of remittance, return of migrants, and investment to sending society. Findings indicate that the research area is the exporter of educated youths to developed countries. When we compare the whole nation it can be concluded that Nepal appear as the periphery in the world economy that exports educated youths to Core Countries like Australia, USA, Japan and many European Countries to fulfill labor shortage in major areas.